Tin Selenide (SnSe): Growth, Properties, and Applications. Issue 4 (8th January 2018) - Shi, Weiran; Gao, Minxuan; Wei, Jinping; Gao, Jianfeng; Fan, Chenwei; Ashalley, Eric; Li, Handong; Wang, Zhiming
Abstract: The indirect bandgap semiconductor tin selenide (SnSe) has been a research hotspot in the thermoelectric fields since a ZT (figure of merit) value of 2.6 at 923 K in SnSe single crystals along the b ‐axis is reported. SnSe has also been extensively studied in the photovoltaic (PV) application for its extraordinary advantages including excellent optoelectronic properties, absence of toxicity, cheap raw materials, and relative abundance. Moreover, the thermoelectric and optoelectronic properties of SnSe can be regulated by the structural transformation and appropriate doping. Here, the studies in SnSe research, from its evolution to till now, are reviewed. The growth, characterization, and recent developments in SnSe research are discussed. The most popular growth techniques that have been used to prepare SnSe materials are discussed in detail with their recent progress. Important phenomena in the growth of SnSe as well as the problems remaining for future study are discussed. The applications of SnSe in the PV fields, Li‐ion batteries, and other emerging fields are also discussed. Abstract : The special crystal structure of tin selenide (both cubic and orthorhombic) and its outstanding thermoelectric and optoelectronic properties attributed to the structure are discussed. Applications and synthesis methods of SnSe materials are concretely summarized to present a comprehensive picture of SnSe.